Artificial Intelligence: What Makes It Different for Language Learning? A Systematic Review - Ma'ruf, Zidni; Tanjung, Ahmad Khoirul Akhir (International Journal of Education, Language, and Religion, 2025)
AI-based language equipment is now heavily used in English learning and teaching because it can offer personal, efficient and interactive educational experience. Therefore, this research aims to explore the advantages and disadvantages of AI in the field of language acquisition by reviewing the literature systematically. Thematic analysis of 22 studies between 2023 and 2025 were included. The results indicate that AI facilitates personalized learning and feedback, time efficiency, learning engagement, skill development, accessibility and teachers’ support. Nevertheless, the review of literature also uncovers a number of limitations including over-dependence on technology, transgressive environment which personifies with a lack in academic integrity and critical thinking, concerns related to data privacy, challenges of accuracy and reliability, pedagogical and technical issues, as well as cultural and language barriers. These findings underscore the need to consider the judicious and ethical use of AI to extend its utility in English language education.